2012
DOI: 10.5923/j.ajcmp.20120203.04
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Annealing on the Size and Morphology of Palladium Nanopaticles

Abstract: Palladiu m(Pd) nanoparticles are produced by variety of methods. In this research, at first Pd nanoparticles were produced by electron beam coating method and then morphology of Pd nanoparticles were studied. Obtained coating can be used as active layer in hydrogen and hydrogen compounds sensors or in hydrogen storage applications. The characterization of the Pd film has been performed by various techniques such as XRD and SEM. The texture and mo rphology of the materials has been investigated by Atomic Force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It was observed that during annealing the resistance of the film initially decreases, after which it starts to increase. This suggests that the film initially becomes a more ordered, more conductive layer, as is described in the scientific literature for various materials, 30,31 possibly through grain growth and the elimination of vacancies before it starts to dewet.…”
mentioning
confidence: 70%
“…It was observed that during annealing the resistance of the film initially decreases, after which it starts to increase. This suggests that the film initially becomes a more ordered, more conductive layer, as is described in the scientific literature for various materials, 30,31 possibly through grain growth and the elimination of vacancies before it starts to dewet.…”
mentioning
confidence: 70%
“…The use of LOF, which can enhance both available P and P uptake, can also improve fertilization efficiency. According to [19], he use of molasses as a fertilizer can promote microbial growth and activity, leading to improved nutrient absorption efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A further annealing step at 325 °C degraded the contact performance. This can be explained by the change of the Pd morphology, specifically by an increasing grain size of Pd at increased temperatures [ 78 ].…”
Section: Reviewmentioning
confidence: 99%